1988
DOI: 10.1246/cl.1988.1239
|View full text |Cite
|
Sign up to set email alerts
|

New Type of Charge-Transfer Complexes between Benzoic Acid 2-[(3,5-Dibromo-4-hydroxyphenyl)-3,5-dibromo-4-oxo-2,5-cyclohexadiene-1-ylidene)methyl]-ethyl Ester (TBPE) and Aliphatic Amines

Abstract: A study has been made of charge–transfer complexes formed between TBPE and aliphatic amines in nonpolar solvents. Large value of the equilibrium constant, large negative values of the heat of reaction as well as the reaction volume indicate that the complex of this type is very stable and the dative structure through hydrogen bonding is predominant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1997
1997
1997
1997

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…We speculate that the hydrogen atom is attracted to tertiary amines because of their higher basicity than other amines in the gas phase and aprotic solvents such as 1,2-DCE, chloroform, and carbon tetrachroride and that it is disconnected from the oxygen atom of the TBPE molecule; the CT band changes depending on the position of the proton. On the other hand, in a previous paper, we showed that, when 1,8-bis( N , N -dimethylamine)naphthalene (Proton Sponge), which has extremely high basicity, was added to HTBPE (yellow) in a nonpolar solvent (benzene), λ max shifted to 620 nm, and the color changed to be blue. It seems that the proton is attracted to the Proton Sponge, and the dissociated ion-pair is formed, as shown in Chart b.…”
Section: Resultsmentioning
confidence: 86%
“…We speculate that the hydrogen atom is attracted to tertiary amines because of their higher basicity than other amines in the gas phase and aprotic solvents such as 1,2-DCE, chloroform, and carbon tetrachroride and that it is disconnected from the oxygen atom of the TBPE molecule; the CT band changes depending on the position of the proton. On the other hand, in a previous paper, we showed that, when 1,8-bis( N , N -dimethylamine)naphthalene (Proton Sponge), which has extremely high basicity, was added to HTBPE (yellow) in a nonpolar solvent (benzene), λ max shifted to 620 nm, and the color changed to be blue. It seems that the proton is attracted to the Proton Sponge, and the dissociated ion-pair is formed, as shown in Chart b.…”
Section: Resultsmentioning
confidence: 86%